We still live among you: colonial continuities, biocultural resistance, and the struggle for environmental justice in Upushwea, the territory of the last Yaghan people - Mansilla, Juan; Soza, Soledad (Frontiers in Human Dynamics, 2026)
This article examines the historical and contemporary struggles of the ancestral inhabitants of Upushwea (Puerto Williams Port), Chile, particularly the Yaghan, Kawéskar, and Selk’nam indigenous peoples, with a particular focus on marine policies affecting the integrity of the Navarino Islands’ reserves. By using the lens of settler colonialism and political ecology, the authors can situate these struggles within the ongoing debates on epistemic violence, neoliberal environmental governance, and the privatization of the commons. The study employs a qualitative approach and an interdisciplinary methodology that combines historiographical analysis, critical political ecology, and interpretive analysis of indigenous oral testimony, with a particular focus on the testimony of an indigenous grandmother as a form of epistemic resistance. The findings demonstrate that colonial logics persist through neoliberal institutions through marine privatization regimes, generating continued dispossession and epistemic erasure. Settler colonialism and the current neoliberal setting continue to reproduce colonial epistemic genocide by marginalizing indigenous knowledge systems while facilitating capitalist expansion into ancestral marine territories. The article argues that recognizing epistemic genocide is crucial for advancing epistemic reparations and environmental justice by acknowledging the existence of indigenous peoples predating settler colonialism in the Chilean Constitution. In line with the UNESCO Convention on the Intangible Cultural Heritage and Chilean legal frameworks, it calls for commons-based governance approaches that protect indigenous biocultural heritage in Upushwea.